Impact of coronavirus disease (Covid-19) within the third trimester of pregnancy - Boychuk, A. V.; Khlibovska, O. I.; Yakymchuk, Y. B. (Journal of Education, Health and Sport, 2020)
Introduction. Assessment of pregnancy, fetal status, diagnosis of placental insufficiency (PI) in pregnant women with coronavirus COVID-19, is a topical issue in obstetric practice and is of great social value for the birth of healthy children. The aim of our study was to analyze the impact of coronavirus disease on pregnancy and fetal status. Methods and materials. An examination of 25 pregnant women who relapsed into Covid-2019, who were treated at Public Non-profit Enterprise Ternopil Municipal City Hospital No. 2. The control group consisted of 25 pregnant women with a physiological course of pregnancy, who gave birth to live full-term infants with mass-growth characteristics according to gestational age. The condition of the fetus was assessed according to ultrasound, cardiotocography. Criteria for inclusion in the study were laboratory confirmed by COVID-19 by polymerase chain reaction (PCR). Results and discussion. It was found that coronavirus disease was present in pregnant women 21 (84.0%) in mild form, 4 (16.0%) patients had pneumonia, but did not require hospitalization and did not require artificial ventilation, and were treated at home by a family doctor. The main complaints of patients were fever in 84.0% (21 pregnant women), cough - in 78.0% (19 pregnant women), myalgia - in 62.0% (15 pregnant women), headache - 84.0% (21 pregnant women) , sore throat - in 40.0% (10 pregnant women), general weakness in 70.0% (17 pregnant women). And 6 pregnant women (20%) of those surveyed had a mild asymptomatic course of the disease. The condition of the fetus was assessed by ultrasound and CTG of the fetus. Decrease in amplitude of oscillations less than 3 beats / min, absence of accelerations, emergence of decelerations, testify to the expressed signs of a hypoxia of a fruit and demand timely treatment and the decision of a question of urgent delivery.